2016
DOI: 10.1158/1078-0432.ccr-16-0449
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hepatic Impairment on Outcomes in Phase I Clinical Trials in Cancer Subjects

Abstract: Purpose The NCI Cancer Therapy Evaluation Program sponsors hepatic dysfunction phase 1 clinical trials (HDCT) and phase 1 clinical trials (P1CT) to determine safe doses and schedules of antineoplastic therapeutics. We sought to compare clinical outcomes between these trial types while stratifying by hepatotoxic agents. Experimental design Individual subject data were extracted from the records of 51 NCI-sponsored HDCT and P1CT. The NCI’s Organ Dysfunction Working Group’s hepatic impairment categorization and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…This review also indicated that organ impairment evaluations represent one of the most common reasons for clinical pharmacology-related PMRs/PMCs, particularly in the setting of hepatic impairment. 8,44 This may reflect the fact that enrollment in organ impairment studies in oncology patients is challenging and may take several years to complete, particularly when enrolling patients with severe impairment. Population PK modeling was used commonly in lieu of dedicated studies to evaluate the effect of at least one category of renal or hepatic impairment, most frequently for monoclonal antibodies.…”
Section: Lessons Learned For Anticancer Drug Developmentmentioning
confidence: 99%
“…This review also indicated that organ impairment evaluations represent one of the most common reasons for clinical pharmacology-related PMRs/PMCs, particularly in the setting of hepatic impairment. 8,44 This may reflect the fact that enrollment in organ impairment studies in oncology patients is challenging and may take several years to complete, particularly when enrolling patients with severe impairment. Population PK modeling was used commonly in lieu of dedicated studies to evaluate the effect of at least one category of renal or hepatic impairment, most frequently for monoclonal antibodies.…”
Section: Lessons Learned For Anticancer Drug Developmentmentioning
confidence: 99%
“…Alisertib is cytotoxic, and so the study was conducted in cancer patients rather than healthy subjects. Thus, the categorization of hepatic impairment was based on the National Cancer Institute Organ Dysfunction Working Group criteria, which are widely used in hepatic impairment studies of antineoplastic agents in cancer patients . A single‐dose study was designed to address the primary objectives based on prior knowledge of alisertib exhibiting linear PK without time dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the categorization of hepatic impairment was based on the National Cancer Institute Organ Dysfunction Working Group criteria, which are widely used in hepatic impairment studies of antineoplastic agents in cancer patients. 16,[21][22][23][24][25][26] A single-dose study was designed to address the primary objectives based on prior knowledge of alisertib exhibiting linear PK without time dependence. However, because the study was conducted in patients with advanced malignancies without treatment options, a multiple-dose phase (7 days' treatment in 21-day cycles) was also part of the protocol to allow potential benefit to patients.…”
Section: Discussionmentioning
confidence: 99%
“…For the multivariate approach, individual pexidartinib exposures were predicted from the individual post hoc PK parameters and then summarized and compared among subgroups of patients who had normal renal function (CRCL ≥90 mL/min), mild (CRCL 60-89 mL/min) or moderate (CRCL 30-59 mL/min) renal impairment, 8 or subgroups of patients with normal hepatic function or mild hepatic impairment according to the National Cancer Institute Organ Dysfunction Working Group classification. 9…”
Section: Evaluation Of Covariate Effects On Pexidartinib and Zaadmentioning
confidence: 99%